Oposiciones binarias revisadas: la naturaleza y la reconciliación de los opuestos en El libro de las pesadillas de Kinnell - Quirós García, Elizabeth (2021)
The book of nightmares, by Galway Kinnell, has been provided with a remarkable use of natural imagery that facilitates the understanding of the lifedeath binary opposition. These two apparently contradictory realms, life and death, are challenging to understand as elements of a unity, since many individuals, especially in Western society, have been taught to appreciate life and disregard death as a real and vital component of this duality. For the purpose of this study the Jungian archetypal approach and Campbell’s perspective onmyth will be discussed. Unquestionably, in this book-length poem, Kinnell succeeds in revealing their ancestral relationship through natural imagery; hence, the persona makes use of images like the rain, the stones of the path, as well as different kind of animals to craft a poetic world to which individuals can relate.